Composite microporous membrane as well as preparation method and application thereof

By using a composite microporous membrane of polymer porous membrane skeleton and hydrophilic inorganic filler, the shortcomings of existing separators in terms of energy consumption, hydrogen production purity and safety are solved, achieving higher ionic conductivity and lower Internal resistance optimizes water electrolysis power and hydrogen production efficiency.

CN119330464AActive Publication Date: 2025-01-21SHANGHAI ENERGY NEW MATERIALS TECHNOLOGY CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411457308.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing separators used for alkaline electrolytic water have shortcomings in energy consumption, hydrogen production purity and use safety. Especially in complex working conditions with frequent start and stop, the hydrogen concentration in oxygen is prone to be too high, which affects the safe operation of the electrolytic system. .

Method used

A polymer is used as the porous membrane skeleton, and hydrophilic inorganic fillers are mixed to form a composite microporous membrane. The membrane includes a hydrophilic base membrane and a coating. The hydrophilic base membrane is made of a first fluoropolymer. The coating is composed of a second fluoropolymer and hydrophilic nanoparticles, which are activated by graft polymerization and irradiation. Steps to Preparation.

Benefits of technology

While ensuring air tightness and ion permeability, the thickness of the diaphragm is reduced, the overall performance of the electrolytic cell is improved, the internal resistance is reduced, the ionic conductivity is improved, the power of electrolyzed water is optimized, the hydrogen production efficiency of the electrolytic cell is enhanced, and the efficiency of the diaphragm is improved. Structural stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330464A_ABST
    Figure CN119330464A_ABST
Patent Text Reader

Abstract

The present invention discloses a composite microporous membrane, which comprises a hydrophilic base membrane and a coating layer coated on a single surface or double surfaces of the hydrophilic base membrane, the hydrophilic base membrane comprises a first fluorine-containing polymer and one or more first hydrophilic grafts grafted on the first fluorine-containing polymer, the coating comprises a second fluorine-containing polymer, one or more second hydrophilic grafts grafted on the second fluorine-containing polymer, and hydrophilic nanoparticles, the first fluorine-containing polymer is the same as the second fluorine-containing polymer, and the composite microporous membrane has low surface resistance, high ionic conductivity and low mass loss rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite diaphragm, in particular to a composite diaphragm for alkaline water electrolysis, and to a slurry and composite membrane process used for manufacturing such diaphragm; the present invention also relates to a fuel cell and an electrolytic hydrogen production device using such diaphragm. Background Art

[0002] The transition from the traditional fossil energy system to sustainable energy is a major trend in the country's energy transformation, which can be achieved by using low-carbon energy and improving energy efficiency. Hydrogen is a carbon-free energy. Due to its wide sources, high flexibility, and rich application scenarios, it has been recognized as an ideal energy carrier for achieving efficient conversion of different energy sources and large-scale development of renewable energy.

[0003] Water electrolysis technology is an efficient and carbon-free method of hydrogen production. Among them, alkaline electrolysis (ALK) is widely used in large-scale green hydrogen production and application due to its high technical maturity, good industrial chain foundation, low investment and large production capacity. At present, ALK commercial electrolysis devices have reached megawatt (GW) scale, and the market capacity is expected to rapidly increase from the current billions to hundreds of billions or even trillions. However, its hydrogen production cost is not yet significantly competitive compared with the cost of hydrogen production from fossil fuels. Generally speaking, the cost of hydrogen production by water electrolysis is greatly affected by electricity costs, so reducing the overall power consumption of the ALK system is of great significance to the promotion of this technology.

[0004] The diaphragm is the core component and key material of the ALK electrolyzer. It not only separates the anode and cathode gases, but also provides an effective channel for the transmission of electrolytes. Its performance directly determines the energy consumption, hydrogen production purity and safety of use of the ALK electrolysis equipment.

[0005] For a long time, the commercial diaphragms used in industrial alkaline electrolyzers in my country have mainly been asbestos cloth and polyphenylene sulfide (PPS) fabric. Asbestos has gradually withdrawn from the electrolyzed water market due to its poor gas barrier properties, high energy consumption and carcinogenic risks. Although PPS has excellent thermal stability, flame retardancy and chemical corrosion resistance, PPS fabric has poor hydrophilicity, large membrane thickness (>700μm) and large through-pore size, and usually exhibits high ionic resistance and permeability, resulting in low hydrogen production efficiency in the electrolyzer. When faced with pressure fluctuations caused by complex operating conditions such as frequent start-stop, the hydrogen concentration in oxygen is prone to be too high, affecting the safe operation of the electrolysis system. Summary of the invention

[0006] Based on the limitations of the above technical means, the main purpose of the present invention is to provide a composite microporous membrane. It uses polymer as the porous membrane skeleton and mixes hydrophilic inorganic fillers to enhance its hydrophilicity. While ensuring the electrochemical performance of the diaphragm, it also has the advantages of both polymer and inorganic components.

[0007] Herein, generally used in the embodiments of the present invention is a composite microporous membrane, which includes a hydrophilic base membrane and a coating applied to one or both sides of the hydrophilic base membrane, wherein the hydrophilic base membrane includes a first fluorine-containing polymer, and the coating includes a second fluorine-containing polymer and hydrophilic nanoparticles, wherein: The first fluoropolymer is identical to the second fluoropolymer.

[0008] Another embodiment of the present invention is a method for preparing a composite microporous membrane, which comprises the following steps: Step S1: Take a base film containing a first fluorinated copolymer and make a plurality of first hydrophilic monomers and / or or a plurality of third hydrophilic monomers are grafted and polymerized on the first fluorine-containing copolymer to form a first hydrophilic graft to obtain a hydrophilic base membrane; Step S2: Take a substrate containing a second fluorinated copolymer and allow a plurality of second hydrophilic monomers and / or or grafting and polymerizing a plurality of fourth hydrophilic monomers on the second fluorinated copolymer to form a second hydrophilic graft to obtain a hydrophilic modified substrate, and dissolving the hydrophilic modified substrate in an organic solvent to obtain a hydrophilic binder solution, wherein the second fluorinated copolymer is the same as the first fluorinated copolymer; Step S3: mixing the hydrophilic binder solution and the hydrophilic nanoparticles to obtain a coating slurry; Step S4: coating the coating slurry on one side or both sides of the first hydrophilic base membrane to obtain the composite microporous membrane.

[0009] In some embodiments, before step S1, the preparation method further comprises step S10: activating the base film by irradiating with a first irradiation amount; before the step S2, the preparation method further comprises a step S20: activating the substrate by irradiating with a second irradiation amount, wherein the irradiation comprises γ Radiation, plasma or electron beam irradiation.

[0010] In the above embodiment, the step of dissolving the hydrophilic substrate comprises: Step S2a: dissolving the hydrophilic substrate in the mixed solvent for a second time at a second temperature, obtaining a pre-hydrophilic binder solution; Step S2b: at a third temperature, replacing the mixed solvent of the pre-hydrophilic binder solution with the organic solvent for a third time to obtain the hydrophilic binder solution.

[0011] In some embodiments, the coating slurry further includes a porogen selected from at least one of PVP, polyethylene glycol, ethanol and n-butanol.

[0012] In some embodiments, the mixed solvent comprises water, a first alcohol solvent and a second alcohol solvent; and the organic solvent comprises at least one of NMP, NEP, DMAC and DMF.

[0013] The embodiments of the composite microporous membrane or the preparation method may further include one or more of the following.

[0014] Generally, based on the total mass of the first fluorine-containing polymer and the first hydrophilic graft, The grafting rate of the first fluorine-containing polymer is 45 to 65%. Based on the total mass of the second fluorine-containing polymer and the second hydrophilic graft, the grafting rate of the second fluorine-containing polymer is 45 to 65%.

[0015] Generally, the first fluorine-containing polymer is grafted with one or more first hydrophilic grafts, which include a first hydrophilic monomer containing a hydroxyl group, a carboxyl group or a heterocyclic aromatic group and / or a third hydrophilic group containing a quaternizable group; and The second fluorine-containing polymer is grafted with one or more second hydrophilic grafts, which include a second hydrophilic monomer containing a hydroxyl group, a carboxyl group or a heterocyclic aromatic group and / or a fourth hydrophilic group containing a quaternizable group, wherein the first hydrophilic monomer is the same as or different from the second hydrophilic monomer, and the third hydrophilic monomer is the same as or different from the fourth hydrophilic monomer.

[0016] Preferably, the first hydrophilic monomer includes at least one or more of acrylic acid monomers, imidazole monomers, acrylate monomers and pyrrolidone monomers; the second hydrophilic monomer includes at least one or more of acrylic acid monomers, imidazole monomers, acrylate monomers and pyrrolidone monomers; the third hydrophilic monomer includes an amide monomer; and the fourth hydrophilic monomer includes an amide monomer.

[0017] Generally, the first fluorine-containing polymer includes any one of polytetrafluoroethylene, polytrifluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyhexafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, and ethylene-tetrafluoroethylene copolymer; the second fluorine-containing polymer includes any one of polytetrafluoroethylene, polytrifluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyhexafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, and ethylene-tetrafluoroethylene copolymer.

[0018] Generally, the hydrophilic nanoparticles include at least one of aluminum oxide, magnesium oxide, calcium oxide, barium oxide, zinc oxide, silicon dioxide, titanium dioxide, zirconium dioxide, magnesium hydroxide, aluminum hydroxide, and boehmite.

[0019] In some embodiments, when the first hydrophilic graft is formed by polymerizing the first hydrophilic monomer and the third hydrophilic monomer, and / or when the second hydrophilic graft is formed by polymerizing the second hydrophilic monomer and the fourth hydrophilic monomer, the preparation method further comprises: Step S5: contacting the composite microporous membrane with a halogenated hydrocarbon at a fourth temperature for a fourth time to obtain a quaternized composite microporous membrane.

[0020] In another embodiment of the present invention, there is a fuel cell comprising a fuel electrode, an air electrode and an ion exchange membrane separated between the fuel electrode and the air electrode, wherein the ion exchange membrane is the aforementioned composite microporous membrane or a composite microporous membrane prepared by the aforementioned preparation method.

[0021] In another embodiment of the present invention, an electrolytic cell includes a cell body, a positive electrode and a negative electrode disposed in the cell body, and a diaphragm separated between the positive electrode and the negative electrode, wherein the diaphragm is the aforementioned composite microporous membrane or a composite microporous membrane prepared by the aforementioned preparation method.

[0022] The beneficial effect obtained by the present invention is that while ensuring the air tightness and ion permeability of the composite microporous membrane, the thickness of the diaphragm is reduced to below 500 μm, which can greatly improve the overall performance of the electrolytic cell and have lower internal resistance and higher ion conductivity; the higher ion conductivity optimizes the electrolysis power of water, allowing the electrolytic cell to produce hydrogen more efficiently.

[0023] In addition, the coating slurry of the composite microporous membrane replaces the hydrophobic binder with a hydrophilic binder, and is coated on the porous skeleton to make the diaphragm have better air tightness than PPS fabric, which can effectively block the anode and cathode gases and ensure the safe operation of the alkaline water electrolyzer; furthermore, the composite microporous membrane has a low mass loss rate, which solves the problem of easy shedding of nanoparticles in the composite membrane coating in the past and improves the structural stability of the diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figures 1A to 1D A series of block flow charts illustrate the specific steps of the preparation method provided by the present invention;

[0025] Figure 2 is a cross-sectional schematic diagram for illustrating the fuel cell structure provided by the present invention; and

[0026] Figure 3 It is a cross-sectional schematic diagram for illustrating the electrolytic cell structure provided by the present invention. DETAILED DESCRIPTION

[0027] The following describes the specific implementation of the present invention by means of several embodiments with accompanying drawings.

[0028] The first embodiment of the present invention is to provide a composite microporous membrane, which includes a hydrophilic base membrane and a coating applied on one or both sides of the hydrophilic base membrane, wherein the hydrophilic base membrane includes a first fluoropolymer, and the coating includes a second fluoropolymer and hydrophilic nanoparticles, wherein the first fluoropolymer is the same as the second fluoropolymer.

[0029] In a general embodiment, based on the total mass of the first fluoropolymer and the first hydrophilic graft, the grafting rate of the first fluoropolymer is 45 to 65%, preferably 50 to 60%; based on the total mass of the second fluoropolymer and the second hydrophilic graft, the grafting rate of the second fluoropolymer is 45 to 65%, preferably 50 to 60%; it can be understood that the hydrophilic grafting rate of the base film and the coating material affects the electrochemical properties of the overall composite microporous membrane. The improvement of the hydrophilic property contributes to the ion conduction of the electrolyte, while improving the filling property of the coating slurry during the coating process and reducing the asymmetry of the surface resistance of the diaphragm; the grafting rate generally refers to the percentage of functional groups introduced into the polymer chain; in this embodiment, the grafting rate of the fluoropolymer can be calculated by the following formula And get:

[0030] In a general embodiment, the surface resistance of the composite microporous membrane is less than 0.3Ω*cm 2 .

[0031] In a general embodiment, the ionic conductivity of the composite microporous membrane is greater than 140 mS*cm -1 , Preferably greater than 170mS*cm -1 , more preferably greater than 185mS*cm -1 .

[0032] In a general embodiment, the composite microporous membrane has a mass loss rate of less than 1% after ultrasonic treatment.

[0033] In a general embodiment, the hydrophilic base membrane is a hydrophilic porous material, and specifically can be a screen, fabric or filter paper.

[0034] In a general embodiment, the first fluorine-containing polymer is grafted with one or more first hydrophilic grafts, which include a first hydrophilic monomer containing a hydroxyl group, a carboxyl group or a heterocyclic aromatic group and / or a third hydrophilic group containing a quaternizable group.

[0035] In a general embodiment, the second fluorine-containing polymer is grafted with one or more second hydrophilic grafts, which include a second hydrophilic monomer containing a hydroxyl group, a carboxyl group or a heterocyclic aromatic group and / or a fourth hydrophilic group containing a quaternizable group.

[0036] As will be appreciated, the hydrophilic graft may be a homopolymer or a copolymer.

[0037] When the hydrophilic graft is a homopolymer, the first hydrophilic graft is a repeating unit derived from the first hydrophilic monomer or the third hydrophilic monomer, and the second hydrophilic graft is a repeating unit derived from the second hydrophilic monomer or the fourth hydrophilic monomer; when the hydrophilic graft is a copolymer, the first hydrophilic graft is a non-repeating unit derived from the first hydrophilic monomer and the third hydrophilic monomer in different arrangement orders and combinations, and the second hydrophilic graft is a non-repeating unit derived from the second hydrophilic monomer and the fourth hydrophilic monomer in different arrangement orders and combinations.

[0038] When the hydrophilic graft is a copolymer, its molecular type can be alternating copolymers, random copolymers, block copolymers or graft copolymers, without particular limitation; in a specific case, the molar ratio of the first hydrophilic monomer to the third hydrophilic monomer is 1:(0.2 to 0.8), preferably 1:(0.22 to 0.7) or 1:(0.25 to 0.67); the molar ratio of the second hydrophilic monomer to the fourth hydrophilic monomer is 1:(0.2 to 0.8), preferably 1:(0.22 to 0.7) or 1:(0.25 to 0.67).

[0039] In the above embodiment, the first hydrophilic monomer may be the same as or different from the second hydrophilic monomer, and the third hydrophilic monomer may be the same as or different from the fourth hydrophilic monomer; in a preferred embodiment, the first hydrophilic monomer is the same as the second hydrophilic monomer, and the third hydrophilic monomer is the same as the fourth hydrophilic monomer.

[0040] In the above embodiment, the first hydrophilic monomer can be one of acrylic monomers, imidazole monomers, amide monomers, acrylate monomers and pyrrolidone monomers; the second hydrophilic monomer can be one of acrylic monomers, imidazole monomers, amide monomers, acrylate monomers and pyrrolidone monomers; the third hydrophilic monomer is any kind of amino ester monomer; the fourth hydrophilic monomer is any kind of amino ester monomer.

[0041] The hydrophilic monomers mentioned above can be specifically listed as follows:

[0042] The acrylic monomers may be, for example, acrylic acid (AA), methacrylic acid (MAA), 2-hydroxypropyl acrylic acid (HPA), methacrylonitrile (Methacrylonitrile), and acrylic acid nitrile (AN), preferably acrylic acid (AA).

[0043] Amide monomers may include, for example, acrylamide (AM), N,N-dimethylacrylamide (DMAA), N-isopropylacrylamide (NIPAM), methacrylamide (MAM), maleimide, N-vinylacetamide, N-vinylformamide, N-acrylpiperazine or N-acrylpyrrolidine.

[0044] The imidazole monomers may be, for example, N-vinyl imidazole (NVI), N-methyl imidazole (1-vinyl-2-methylimidazole), 1-(3-aminopropyl) imidazole (N-(3-aminopropyl)-imidazole) or 1-vinyl-3-methylimidazole (1-vinyl-3-methylimidazole).

[0045] The acrylate monomers may be, for example, 2-Hydroxyethyl Methacrylate (HEMA), methyl methacrylate (EMA), n-butyl methacrylate (n-Butyl Methacrylate, n-BMA), methyl acrylate (MA), ethyl acrylate (EA), glycidyl methacrylate (GMA), isopropyl acrylate (IPA), benzyl acrylate (BzA), n-butyl acrylate (n-BA) or isobutyl methacrylate (iBMA), preferably 2-Hydroxyethyl Methacrylate (HEMA).

[0046] Pyrrolidone monomers can be, for example, N-vinylpyrrolidone (NVP), N-Methylpyrrolidone (NMP) or 2-pyrrolidone (2-Pyrrolidone).

[0047] Examples of the aminoester monomer include dimethylaminoethyl methacrylate (DMAEMA), diethylaminoethyl methacrylate (DEAEMA), dimethylaminoethyl acrylate (DMAEA), diethylaminoethyl acrylate (DEAEA), N,N-dimethylaminopropyl acrylate (DMAAP), or N,N-dimethylaminopropyl methacrylate (DMAPMA), preferably dimethylaminoethyl methacrylate (DMAEMA).

[0048] In a general embodiment, the first fluorine-containing polymer includes any one of polytetrafluoroethylene, polytrifluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyhexafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, and ethylene-tetrafluoroethylene copolymer, and is preferably an ethylene-tetrafluoroethylene copolymer; the second fluorine-containing polymer includes any one of polytetrafluoroethylene, polytrifluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyhexafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, and ethylene-tetrafluoroethylene copolymer, and is preferably an ethylene-tetrafluoroethylene copolymer.

[0049] In a general embodiment, the hydrophilic nanoparticles include at least one of aluminum oxide, magnesium oxide, calcium oxide, barium oxide, zinc oxide, silicon dioxide, titanium dioxide, zirconium dioxide, magnesium hydroxide, aluminum hydroxide, and boehmite, preferably zirconium dioxide.

[0050] See also Figure 1A The second embodiment of the present invention provides a method for preparing a composite microporous membrane. It includes the following steps: Step S1: Take a base film containing a first fluorinated copolymer and make a plurality of first hydrophilic monomers and / or or a plurality of third hydrophilic monomers are grafted and polymerized on the first fluorine-containing copolymer to form a first hydrophilic graft to obtain a hydrophilic base membrane; Step S2: Take a substrate containing a second fluorinated copolymer and allow a plurality of second hydrophilic monomers and / or or grafting a plurality of fourth hydrophilic monomers onto the second fluorine-containing copolymer to form a second hydrophilic graft to obtain a hydrophilic modified substrate, and dissolving the hydrophilic modified substrate in an organic solvent to obtain a hydrophilic binder solution; Step S3: mixing the hydrophilic binder solution and the hydrophilic nanoparticles to obtain a coating slurry; Step S4: coating the coating slurry on one side or both sides of the first hydrophilic base membrane to obtain the composite microporous membrane.

[0051] In a general embodiment, the second fluorinated copolymer is the same as the first fluorinated copolymer.

[0052] In a general embodiment, the base membrane is a porous material including a screen, a fabric or a filter paper. The substrate may be a porous material similar to the base film, or a raw material used to form the base film, such as powder, fiber or slurry.

[0053] In a general embodiment, the solid content of the coating slurry is 10 to 20 wt%, preferably 10 to 15 wt% or 15 to 20 wt%.

[0054] In a general embodiment, the mass ratio of the hydrophilic modified substrate to the hydrophilic nanoparticles is 1:(3 to 8), preferably 1:(4 to 6).

[0055] In a general embodiment, the coating slurry further includes a porogen selected from at least one of PVP, polyethylene glycol, ethanol and n-butanol.

[0056] In a general embodiment, the organic solvent may be at least one of N-methylpyrrolidone (NMP), N-ethylpyrrolidone (NEP), N,N-dimethylacetamide (DMAC) and dimethylformamide (DMF).

[0057] In a general embodiment, the polymerization grafting reaction is carried out at a first temperature of 40 to 80° C. for a first time of 30 to 90 minutes, preferably at 50 to 60° C. for 50 to 70 minutes.

[0058] See also Figure 1B In some embodiments, in order to activate the base film and the substrate to generate free radicals for the subsequent free radical grafting polymerization reaction, before the step S1, the preparation method further includes a step S10: activating the base film with a first irradiation amount; and / or before the step S2, the preparation method further includes a step S20: activating the substrate with a second irradiation amount, wherein the irradiation includes γ-ray irradiation, plasma irradiation or electron beam irradiation.

[0059] In some embodiments, the irradiation is electron beam irradiation, and the first irradiation dose is 40 to 200 kGy, preferably 60 to 120 kGy; the second irradiation dose is 40 to 200 kGy, preferably 60 to 120 kGy; preferably, the first irradiation dose is the same as the second irradiation dose.

[0060] See also Figure 1C In a general embodiment, the step of dissolving the hydrophilic substrate includes the following sub-steps: Step S2a: dissolving the hydrophilic substrate in the mixed solvent for a second time at a second temperature to obtain a pre-hydrophilic binder solution; and Step S2b: at a third temperature, replacing the mixed solvent of the pre-hydrophilic binder solution with the organic solvent for a third time to obtain the hydrophilic binder solution.

[0061] In the above embodiment, the hydrophilic substrate is dissolved at a second temperature of 100 to 300° C. for at least 5 hours, and the pre-hydrophilic binder solution is solvent-exchanged at a third temperature below 80° C. for 4 to 36 hours, preferably 12 to 24 hours.

[0062] In the above embodiment, the mixed solvent is an alcohol aqueous solution, which includes water, a first alcohol solvent and a second alcohol solvent, wherein the first alcohol solvent is, for example, n-propanol, isopropanol, n-butanol, isobutanol or a mixture thereof, and the second alcohol solvent is, for example, methanol or ethanol; in some specific cases, the mixing ratio of the water, the first alcohol solvent and the second alcohol solvent is 3:(3 to 5):(1 to 2), preferably 3:(3.5 to 4.0):(1.1 to 1.3).

[0063] In some embodiments, when the first hydrophilic graft is polymerized from the first hydrophilic monomer and the third hydrophilic monomer, and / or when the second hydrophilic graft is polymerized from the second hydrophilic monomer and the fourth hydrophilic monomer, the quaternizable groups in the composite microporous membrane may be further quaternized to enhance the overall hydrophilicity; accordingly, see Figure 1D The preparation method further includes step S5: contacting the composite microporous membrane with a halogenated hydrocarbon for a fourth time at a fourth temperature to obtain a quaternized composite microporous membrane, wherein the fourth temperature is 50 to 200°C, preferably 60 to 100°C, the fourth time is 4 to 16 hours, preferably 8 to 10 hours, and the halogenated hydrocarbon includes one or more of methyl iodide, ethyl bromide, butyl bromide, and hexyl bromide, preferably methyl iodide.

[0064] See also Figure 2 The third embodiment of the present invention provides a fuel cell (100), which includes a fuel electrode (1), an air electrode (2) and an ion exchange membrane (3) separated between the fuel electrode (1) and the air electrode (2), wherein the ion exchange membrane (3) is the composite microporous membrane provided in the first embodiment or the composite microporous membrane prepared by the preparation method provided in the second embodiment.

[0065] See also Figure 3 The fourth embodiment of the present invention provides an electrolytic cell (200), which includes a cell body (2a) and a positive electrode (10), a negative electrode (20) arranged in the cell body (2a), and a diaphragm (30) separated between the positive electrode (10) and the negative electrode (20), wherein the diaphragm (30) is the composite microporous membrane provided in the first embodiment or the composite microporous membrane prepared by the preparation method provided in the second embodiment.

[0066] In a general embodiment, the water electrolysis power of the electrolytic cell (200) is greater than 0.55 W, preferably greater than 0.65 W, and more preferably greater than 0.75 W under the condition of a cell voltage of 1.5 to 2.0 V.

[0067] Several embodiments are provided below to illustrate the technical effects achieved by the present invention, but are not intended to limit the present invention.

[0068] Example 1

[0069] Step S10: Take ETFE fabric of 5×10 cm and thickness of 290 μm, activate it with 100 kGy electron beam, and then store it at -25°C for later use.

[0070] Step S1: Add 60 g of DMF and 40 g of hydroxyethyl methacrylate (HEMA) to a double-layer glass reactor connected to a reflux device, continue stirring and introduce nitrogen to remove air from the solution, and after 20 minutes, heat the reaction solution to 60°C; add activated ETFE fabric, and graft react for 60 minutes, then take out HEMA grafted modified ETFE fabric (hereinafter referred to as ETFE-g-pHEMA) was repeatedly rinsed with isopropanol.

[0071] Step S2: Take ETFE fabric of 2×2 cm and thickness of 290 μm and repeat steps S10 to S1. Obtain ETFE-g-pHEMA; weigh 1 unit weight of ETFE-g-pHEMA, mix it with a mixed solvent (water, n-propanol, ethanol unit weight ratio = 3:3.8:1.2) in a reaction kettle, and dissolve it at 230°C for 5 hours to obtain a pre-hydrophilic binder solution with a solid content of 10%; pour the pre-hydrophilic binder solution into a separatory funnel and let it stand for 24 hours, take the lower half of the solution, and evaporate it at 80°C for solvent replacement to obtain a NMP solution with a solid content of 20% as a hydrophilic binder solution.

[0072] Step S3: Under an environment with a humidity of no more than 40%, weigh 62 g of a hydrophilic adhesive solution and 37.2 Grams of zirconium dioxide (ZrO2) were added and stirred at 750 r / min for 2 hours, then 0.8 grams of PVP was added, and the mixture was stirred at 750 r / min for another 2 hours, and degassed to obtain a coating slurry.

[0073] Step S4: Double-sided coating of the coating slurry on the ETFE-g-pHEMA obtained in step 1, with a wet film thickness of about 800 μm, followed by heat treatment at 140° C. for 10 minutes, and vertically immersion in a non-solvent phase with a water-to-alcohol mass ratio of 1:1 for 20 minutes to obtain a composite microporous membrane.

[0074] Example 2

[0075] The method and steps are substantially the same as those in Example 1, except that HEMA is replaced by acrylic acid (AA) to obtain AA grafted modified ETFE fabric (ETFE-g-pAA).

[0076] Example 3

[0077] The method steps are substantially the same as those in Example 1, except that 29.2 g of HEMA and 10.8 g of AA are added in step S1 to obtain HEMA-AA copolymer grafted modified ETFE fabric (ETFE-gp(HEMA-co-AA)); and step S2 obtains a 10% solid content NMP solution as a hydrophilic binder solution.

[0078] Example 4

[0079] The method steps are substantially the same as those in Example 1, except that: In step S1, 30.7 g of HEMA and 9.3 g of DMAEMA are added to obtain HEMA-DMAEMA copolymer grafted modified ETFE fabric (ETFE-gp(HEMA-co-DMAEMA)); Step S2: obtaining a NMP solution with a solid content of 10% as a hydrophilic binder solution; and After step S4, there is further step S5: immersing the composite microporous membrane obtained in step 4 in an ethanol solution containing 0.2M iodomethane, reacting at 60°C for 10 hours to obtain a quaternized composite microporous membrane, and repeatedly washing with isopropanol.

[0080] Example 5

[0081] The method steps are substantially the same as those in Example 1, except that boehmite is added in step S3.

[0082] Comparative Example 1

[0083] The method steps are substantially the same as those in Example 1, except that the ETFE fabric is not subjected to grafting modification.

[0084] Comparative Example 2

[0085] The method steps are substantially the same as those in Example 1, except that the ETFE fabric is activated with 30 kGy electron beam.

[0086] Comparative Example 3

[0087] The method steps are substantially the same as those in Example 1, except that the grafting reaction lasts for 30 minutes.

[0088] Comparative Example 4

[0089] The method steps are substantially the same as those in Example 1, except that in step 1 S2, 2×2 cm PVDF with a thickness of 290 μm is taken to perform steps S10 to S1 to obtain PVDF-g-pHEMA, and the hydrophilic binder solution is prepared therefrom.

[0090] Comparative Example 5

[0091] The method steps are substantially the same as those in Example 1, except that 100 g of a hydrophilic binder solution is added in step S3, and zirconium dioxide (ZrO 2 ) is not added.

[0092] Comparative Example 6

[0093] The method steps are substantially the same as those in Example 1, except that the ETFE fabric is activated with 200 kGy electron beam.

[0094] Comparative Example 7

[0095] The method steps are substantially the same as those in Example 1, except that the grafting reaction lasts for 120 minutes.

[0096] Sheet resistance and ionic conductivity

[0097] Take a composite microporous membrane of a certain thickness of 2.5*2.5cm (the test area is a circle with a diameter of 2cm) and After being immersed in KOH for 24 hours, it was placed in a stainless steel test chamber and the impedance spectrum of the composite microporous membrane was obtained using an electrochemical workstation. The reading of the intersection of the high-frequency part of the spectrum line and the real axis was taken as the impedance value, which was then converted into surface resistance and ionic conductivity.

[0098] Quality loss rate

[0099] The composite microporous membrane of 5×5 cm was dried at 100℃ for 1 hour and its mass W1 was weighed. It was treated with 360W ultrasonic wave for 5 minutes and then dried at 100℃ for 1 hour and its mass W2 was weighed. The mass loss rate is calculated by the following formula:

[0100] Alkaline electrolyzed water test

[0101] Active area 15cm 2 The LSCF single stack is an electrolyzer, and the diaphragm is replaced by a composite microporous membrane. 30% KOH is used as the electrolyte, and the cell pressure is 1.5 to 2.0 at 80°C and powered by a DC power supply. V, step size 0.05V, current density 0.4A*cm-2 After running for 200 hours, the voltammetric curve of the composite microporous membrane was tested, and the power of the system at 1.8V was calculated.

[0102] After the individual embodiments and comparative examples passed the above tests, the test results obtained are summarized in Table 1.

[0103] It can be seen from the comparison between Examples 1 to 5 and Comparative Example 1 that after the base film and coating materials are hydrophilically modified, the performance of the composite microporous membrane is significantly improved. It not only reduces the surface resistance to 0.3Ω*cm 2 The ionic conductivity is increased by at least 30.8%, 52.6%, 41.3%, 45.1% and 27.1% respectively, and the mass loss rate after ultrasonic action is also reduced to below 1%, and the electrolytic water power is enhanced by at least 43%. Table 1

[0104] By comparing Examples 1 to 5 with Comparative Examples 2 and 3, it can be seen that the grafting rate of the hydrophilic grafts in the base membrane and coating materials also directly affects the performance of the composite microporous membrane in various aspects. The low irradiation dose (30 kGy) and the shorter polymerization time (30 minutes) produce a lower grafting rate, and there is no significant improvement in surface resistance, ionic conductivity, mass loss rate and electrolytic water power.

[0105] On the other hand, compared with Example 1, Comparative Example 4 illustrates that the preparation of the base film and the coating with different substrates actually results in a lower mass loss rate; in Comparative Example 5, under the condition that the coating lacks nanoparticles, its conductive properties are greatly reduced; in Comparative Example 6, although the grafting rate is significantly improved by activating the ETFE fabric with a high irradiation dose (200 kGy), the mass loss rate and the electrolytic water power are not significantly improved; similarly, in Comparative Example 7, the grafting rate is increased by extending the grafting reaction time (120 minutes), and its mass loss rate does not decrease but increases, and the electrolytic water power is not significantly improved.

[0106] The above contents involving common knowledge are not described in detail, and those skilled in the art can understand them.

[0107] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A composite microporous membrane, characterized in that: The composite microporous membrane includes a hydrophilic base membrane and a coating coated on one or both sides of the hydrophilic base membrane, wherein the hydrophilic base membrane includes a first fluoropolymer and one or more first hydrophilic grafts grafted thereon, and the coating includes a second fluoropolymer and one or more second hydrophilic grafts grafted thereon, and hydrophilic nanoparticles, wherein the first fluoropolymer is the same as the second fluoropolymer.

2. The composite microporous membrane according to claim 1, characterized in that Based on the total mass of the first fluorine-containing polymer and the first hydrophilic graft, the grafting rate of the first fluorine-containing polymer is 45 to 65%; based on the total mass of the second fluorine-containing polymer and the second hydrophilic graft, the grafting rate of the second fluorine-containing polymer is 45 to 65%.

3. The composite microporous membrane according to claim 1 or 2, characterized in that: The first hydrophilic graft comprises a first hydrophilic monomer containing a hydroxyl group, a carboxyl group or a heterocyclic aromatic group and / or a third hydrophilic monomer containing a quaternizable group; and The second hydrophilic graft comprises a second hydrophilic monomer containing a hydroxyl group, a carboxyl group or a heterocyclic aromatic group and / or a fourth hydrophilic monomer containing a quaternizable group, wherein the first hydrophilic monomer is the same as or different from the second hydrophilic monomer, and the third hydrophilic monomer is the same as or different from the fourth hydrophilic monomer.

4. The composite microporous membrane according to claim 3, characterized in that: The first hydrophilic monomer includes at least one or more of acrylic acid monomers, imidazole monomers, amide monomers, acrylate monomers and pyrrolidone monomers; The second hydrophilic monomer includes at least one or more of acrylic acid monomers, imidazole monomers, amide monomers, acrylate monomers and pyrrolidone monomers; The third hydrophilic monomer includes an aminoester monomer; The fourth hydrophilic monomer includes an aminoester monomer.

5. The composite microporous membrane according to claim 4, characterized in that: The acrylic acid-based monomer includes acrylic acid (AA), the acrylate-based monomer includes hydroxyethyl methacrylate (HEMA), and the amino ester-based monomer includes dimethylaminoethyl methacrylate (DMAEMA).

6. The composite microporous membrane according to claim 1 or 2, characterized in that: The first fluorine-containing polymer includes any one of polytetrafluoroethylene, polytrifluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyhexafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, and ethylene-tetrafluoroethylene copolymer; The second fluorine-containing polymer includes any one of polytetrafluoroethylene, polytrifluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyhexafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, and ethylene-tetrafluoroethylene copolymer.

7. The composite microporous membrane according to claim 1 or 2, characterized in that: The hydrophilic nanoparticles include at least one of aluminum oxide, magnesium oxide, calcium oxide, barium oxide, zinc oxide, silicon dioxide, titanium dioxide, zirconium dioxide, magnesium hydroxide, aluminum hydroxide, and boehmite.

8. A method for preparing a composite microporous membrane, characterized in that: The following steps are involved: Step S1: taking a base film containing a first fluorinated copolymer, and grafting a plurality of first hydrophilic monomers and / or a plurality of third hydrophilic monomers onto the first fluorinated copolymer to form a first hydrophilic graft, so as to obtain a hydrophilic base film; Step S2: taking a substrate containing a second fluorinated copolymer, grafting and polymerizing a plurality of second hydrophilic monomers and / or a plurality of fourth hydrophilic monomers on the second fluorinated copolymer to form a second hydrophilic graft to obtain a hydrophilic modified substrate, and dissolving the hydrophilic modified substrate in an organic solvent to obtain a hydrophilic binder solution, wherein the second fluorinated copolymer is the same as the first fluorinated copolymer; Step S3: mixing the hydrophilic binder solution and the hydrophilic nanoparticles to obtain a coating slurry; Step S4: coating the coating slurry on one side or both sides of the first hydrophilic base membrane to obtain the composite microporous membrane.

9. The preparation method according to claim 8, characterized in that: Based on the total mass of the first fluorine-containing polymer and the first hydrophilic graft, the grafting rate of the first fluorine-containing polymer is 45 to 65%; based on the total mass of the second fluorine-containing polymer and the second hydrophilic graft, the grafting rate of the second fluorine-containing polymer is 45 to 65%.

10. The preparation method according to claim 8 or 9, characterized in that: Before the step S1, the preparation method further comprises a step S10: activating the base film by irradiating with a first irradiation amount; Before the step S2, the preparation method further comprises a step S20: activating the substrate by irradiating with a second irradiation amount, wherein the irradiation comprises gamma ray irradiation, plasma irradiation or electron beam irradiation.

11. The preparation method according to claim 8 or 9, characterized in that: The polymerization grafting reaction is performed at a first temperature of 40 to 80° C. for a first time of 30 to 90 minutes.

12. The preparation method according to claim 8 or 9, characterized in that: The first hydrophilic monomer includes a hydroxyl group, a carboxyl group or a heterocyclic aromatic group; The third hydrophilic monomer includes a quaternizable group; The second hydrophilic monomer includes a hydroxyl group, a carboxyl group or a heterocyclic aromatic group; The fourth hydrophilic monomer includes a quaternizable group, wherein the first hydrophilic monomer is the same as or different from the second hydrophilic monomer, and the third hydrophilic monomer is the same as or different from the fourth hydrophilic monomer.

13. The preparation method according to claim 12, characterized in that: The first hydrophilic monomer includes at least one or more of acrylic acid monomers, imidazole monomers, amide monomers, acrylate monomers and pyrrolidone monomers; The second hydrophilic monomer includes at least one or more of acrylic acid monomers, imidazole monomers, amide monomers, acrylate monomers and pyrrolidone monomers; The third hydrophilic monomer includes an aminoester monomer; The fourth hydrophilic monomer includes an aminoester monomer.

14. The preparation method according to claim 13, characterized in that: The acrylic acid-based monomer includes acrylic acid (AA), the acrylate-based monomer includes hydroxyethyl methacrylate (HEMA), and the amino ester-based monomer includes dimethylaminoethyl methacrylate (DMAEMA).

15. The preparation method according to claim 13, characterized in that: When the first hydrophilic graft is formed by polymerizing the first hydrophilic monomer and the third hydrophilic monomer, and / or when the second hydrophilic graft is formed by polymerizing the second hydrophilic monomer and the fourth hydrophilic monomer, the preparation method further comprises: Step S5: contacting the composite microporous membrane with a halogenated hydrocarbon for a fourth time to obtain a quaternized composite microporous membrane, wherein the halogenated hydrocarbon comprises one or more of iodomethane, ethyl bromide, butyl bromide, and hexyl bromide.

16. The preparation method according to claim 8 or 9, characterized in that: The first fluorine-containing polymer includes any one of polytetrafluoroethylene, polytrifluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyhexafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, and ethylene-tetrafluoroethylene copolymer; the second fluorine-containing polymer includes any one of polytetrafluoroethylene, polytrifluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyhexafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, and ethylene-tetrafluoroethylene copolymer.

17. The preparation method according to claim 8 or 9, characterized in that: The hydrophilic nanoparticles include at least one of aluminum oxide, magnesium oxide, calcium oxide, barium oxide, zinc oxide, silicon dioxide, titanium dioxide, zirconium dioxide, magnesium hydroxide, aluminum hydroxide, and boehmite.

18. The preparation method according to claim 8 or 9, characterized in that: The coating slurry further includes a porogen selected from at least one of polyvinyl pyrrolidone (PVP), polyethylene glycol, ethanol and n-butanol.

19. A fuel cell, characterized in that: The fuel cell comprises a fuel electrode, an air electrode and an ion exchange membrane separated between the fuel electrode and the air electrode, and the ion exchange membrane diaphragm is the composite microporous membrane described in claim 1 or 2 or the composite microporous membrane prepared by the preparation method described in claim 8 or 9.

20. An electrolytic cell, characterized in that: The electrolytic cell comprises a cell body and a positive electrode and a negative electrode arranged in the cell body, and a diaphragm separated between the positive electrode and the negative electrode. The diaphragm is the composite microporous membrane described in claim 1 or 2 or a composite microporous membrane prepared by the preparation method described in any one of claims 8 or 9.

Citation Information

Patent Citations

  • Method of amphipathic nature fluorine-contained copolymer modifying surface of polytetrafluoroethylene porous membrane

    CN101108313A

  • Nano plasma modified fluorine-containing highly weather-resistant solar cell back film and production process thereof

    CN102569464A

  • High-wettability composite diaphragm and preparation method thereof

    CN114530669A

  • Composite ion exchange membrane and preparation method thereof

    CN114976165A

  • High proton transport exchange membrane for vanadium battery as well as preparation method and application of high proton transport exchange membrane

    CN115939477A